Neuroblastoma Origin and Therapeutic Targets for Immunotherapy - Irina V. Kholodenko; Daniel V. Kalinovsky; Igor I. Doronin; Sergey M. Deyev; Roman V. Kholodenko (Journal of Immunology Research)
Neuroblastoma is a pediatric solid cancer of heterogeneous clinical behavior. The unique features of this type of cancer frequently hamper the process of determining clinical presentation and predicting therapy effectiveness. The tumor can spontaneously regress without treatment or actively develop and give rise to metastases despite aggressive multimodal therapy. In recent years, immunotherapy has become one of the most promising approaches to the treatment of neuroblastoma. Still, only one drug for targeted immunotherapy of neuroblastoma, chimeric monoclonal GD2-specific antibodies, is used in the clinic today, and its application has significant limitations. In this regard, the development of effective and safe GD2-targeted immunotherapies and analysis of other potential molecular targets for the treatment of neuroblastoma represents an important and topical task. The review summarizes biological characteristics of the origin and development of neuroblastoma and outlines molecular markers of neuroblastoma and modern immunotherapy approaches directed towards these markers.